1989
DOI: 10.1099/0022-1317-70-10-2683
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Stomatitis Virus RNA Replication: a Role for the NS Protein

Abstract: SUMMARYSynthesis of the vesicular stomatitis virus nucleocapsid (N) protein is required for viral RNA replication. The observation that the N protein forms a rapidly sedimenting species in the absence of other viral proteins and the description of complexes of N protein with NS protein led to the proposal that NS protein binds to N protein to prevent it from self-associating. We tested this model by analysing the physical properties of N protein synthesized alone in an in vitro replication system as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 25 publications
4
74
0
Order By: Relevance
“…There is general agreement that the phosphoprotein (P) keeps N in a soluble form, able to support replication (Davis et al, 1986 ;Peluso, 1988 ;Masters & Banerjee, 1988 a, b ;Peluso et al, 1988 ;Howard & Wertz, 1989 ;Pre! haud et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…There is general agreement that the phosphoprotein (P) keeps N in a soluble form, able to support replication (Davis et al, 1986 ;Peluso, 1988 ;Masters & Banerjee, 1988 a, b ;Peluso et al, 1988 ;Howard & Wertz, 1989 ;Pre! haud et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the NP362 oligomers banded at a buoyant density of 1n27 g\cm$ (Fig. 5 E), reproducibly lighter than wt NP suggesting that they are not associated with RNA (Blumberg et al, 1983 ;Howard & Wertz, 1989). The population of NP362 molecules at the top of the gradient (fractions 2-4) most likely represents monomeric protein that has not reached equilibrium under these centrifugation conditions.…”
Section: Self-assembly Is Altered In the Np Mutantsmentioning
confidence: 93%
“…The roles of P NTD in binding L and of P CTD in binding N-RNA were first recognized by biochemical and genetic studies, establishing a primary role of P as a mediator of L's access to the N-RNA template (11). A second essential role of P involves chaperoning the free N protein (N 0 ) via the extreme N terminus of P NTD , maintaining N 0 solubility and regulating its assembly on the nascent genomic RNA during replication (16,17).An expanding structural map of P is beginning to provide additional functional insight into its role in RNA synthesis. Analysis of the crystal structure of the VSV P CTD has shown that P CTD makes direct contact with the C-terminal lobes of two adjacent N protomers (18).…”
mentioning
confidence: 99%
“…The roles of P NTD in binding L and of P CTD in binding N-RNA were first recognized by biochemical and genetic studies, establishing a primary role of P as a mediator of L's access to the N-RNA template (11). A second essential role of P involves chaperoning the free N protein (N 0 ) via the extreme N terminus of P NTD , maintaining N 0 solubility and regulating its assembly on the nascent genomic RNA during replication (16,17).…”
mentioning
confidence: 99%